(untitled) (Pedagogy of Higher and Secondary Education, 2003)
Communicative individual approach to the lesson of Russian: The problem of teaching Russian as a foreign language. Modern development oflinguodidactics is characterized by the intensive introduction of the concept of communicative and student-oriented teaching. The articles deal with the problems of the development of students ’ communicative competence, with the strategy of teaching Russian as a foreign language, with the structure of the lesson of Russian taking into account the communicative and student-oriented approach.